Sideways arithmetic from Wayside School - Sachar, Louis, 1954- (New York : Scholastic, 2004)
Contains over fifty math puzzles and brainteasers.
"An Apple paperback."
Answers: p.75-p.89.
Booklist
3-6
English.
Keywords: Mathematics -- Problems, exercises, etc. -- Juvenile literature; Mathematics -- Problems, exercises, etc; Mathematics -- Problems, exercises, etc